Review: Government Policy against Former Followers of International Terrorist Organizations - Iswandi, Andi (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2022)
The purpose of this study is to analyze the legal status of citizenship of ex ISIS and analyze government policies and compare the implementation of policies with other countries. The author uses library research methods , techniques and deductive approaches , to analyze cases and regulatory problems in various phenomena . Legal information is obtained from primary, secondary, and tertiary sources. In this paper, the author applies the theory of state ownership, state responsibility, and citizens. The results of the study found that citizenship status is a fundamental right for everyone . This right cannot be exercised without a state legal framework, and the state must consider the consequences of revocation of citizenship as long as citizens want to return to being good citizens and loyal to the state. The state must protect the basic rights of individuals as regulated by domestic law and international law.